Collaboration patterns and patenting in nanotechnology: exploring gender distinctions - Meng, Yu (Georgia Institute of Technology, 2013)
Drawing upon the research on gender in science (especially gender and publication and patent productivity), social network studies, and social studies of interdisciplinary research and nanotechnology, this dissertation develops and tests a series of hypotheses to advance the understanding of the gender difference in patenting in the U.S. Ridgeways theory of gender frame (Ridgeway, 2009, 2007; Ridgeway&England, 2004) is very powerful in explaining gender inequity at both micro- and macro-levels, and thus constitutes the foundation of this study. After laying out the theoretical foundation, I set out to focus on collaboration as one of critical mechanisms accounting for the gender difference in patenting.